2-{1-[(2-Nitrobenzenesulfonamido)methyl]cyclohexyl}acetic acid - Nosheen Kanwal; Erum Akbar Hussain; Onur Şahin; Orhan Büyükgüngör (Acta Crystallographica Section E, 2012)
In the title compound, C15H20N2O6S, the C—SO2—NH—C torsion angle is 64.54 (14)°. In the molecule, there is a bifurcated N—H...(O,O) hydrogen bond, forming S(7) rings. In the crystal, inversion dimers are formed via O—H...O hydrogen bonds involving the carboxyl group, so forming R22(8) rings. These dimers are further linked via pairs of C—H...O hydrogen bonds, forming a C(6) chain propagating along the c-axis direction.